BIVALVE RESOURCES IN THE COASTAL WATERS OF BINH THUAN PROVINCE (VIET NAM) AND THEIR RELATIONSHIP WITH THE STRONG UPWELLING - Tuan, Vo Si; Tuyen, Hua Thai (Vietnam Journal of Marine Science and Technology, 2009)
Based on analysis of the published papers and data obtained by different projects implemented during 1990 - 2005, it is highlighted that the coastal waters of Binh Thuan Province (South Viet Nam) are characterised by the abundant distribution of sublitoral bivalves, including inter alia: Chlamys nobilis, Anadara antiquata, Modiolus philippinarum, Paphia undulata and Pinna sp. The richness of nutrients provided by the strong upwelling and its direct ecological effect - abundance of phytoplankton (and possible material transformation following strong upwelling) are considered as favourable factors for growth and high biomass of these bivalves. Levels of the relation with ecological effects of the strong upwelling change among species due to differences on population ecology of the species. The Scallop C. nobilis depends on the strong upwelling at the highest level and seconded by mussel M. philippinarum. The clams A. antiquata and P. undulata are influenced by factors caused by upwelling and river discharge. It is able to wrap up that changes in position and intensity of the strong upwelling would control biological processes and as a result, fluctuation of population biomass of these species in the coastal waters of Binh Thuan province.